2018
DOI: 10.1016/j.rmed.2018.07.012
|View full text |Cite
|
Sign up to set email alerts
|

30-year trends in asthma and the trends in relation to hospitalization and mortality

Abstract: There was an increasing trend in the prevalence of asthma and a declining trend in hospitalization, especially in asthmatic subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 36 publications
3
18
0
Order By: Relevance
“…Similarly, 54 320 adult subjects were examined in seven independent crosssectional population surveys repeated every ve years between 1982 and 2012 in Finland. All-cause mortality decreased between 1982 and 2015, though mortality in asthmatic subjects compared with nonasthmatics was higher from all causes 22 . Another study from Finland looked at a smaller number of patients over the age of 30.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, 54 320 adult subjects were examined in seven independent crosssectional population surveys repeated every ve years between 1982 and 2012 in Finland. All-cause mortality decreased between 1982 and 2015, though mortality in asthmatic subjects compared with nonasthmatics was higher from all causes 22 . Another study from Finland looked at a smaller number of patients over the age of 30.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, 54,320 adult subjects were examined in seven independent cross-sectional population surveys repeated every 5 years between 1982 and 2012 in Finland. All-cause mortality decreased between 1982 and 2015, though mortality in asthmatic subjects compared with non-asthmatics was higher from all causes [22]. Another study from Finland looked at a smaller number of patients over the age of 30.…”
Section: Discussionmentioning
confidence: 99%
“…Pelkonen et al, 2018, reported that hospitalized asthmatic patients without airway flow limitations did not have higher mortality than those with chronic obstructive pulmonary disease ( p = 0.001) [ 14 ]. The UK National Review of Asthma Deaths (NRAD) studied 900 deaths of people of all ages in 2012 under ICD-10 code J459.…”
Section: Introductionmentioning
confidence: 99%